Online Game Addiction Behavior in Generation Z - Diea Mila Agustin; Abelia Seprianti; Khoirani Khoirani; Muhammad Rafli Akbar; Alrefi Alrefi; Akbari Akbari (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
This research aimed to analyze online game addiction behavior in generation Z, who were increasingly involved in the use of digital technology. Online game addiction had caused various negative impacts, especially on mental, physical and social health, such as aggressiveness, decreased motivation to learn, social isolation and emotional disorders. This research used a literature review method by examining the results of previous research in the period 2015-2024. The research results showed that online game addiction affected individuals, both in urban and rural settings, with reduced youth participation in social and academic activities. However, besides negative impacts, online games also had several positive benefits if used wisely, such as improving technological skills, mastery of foreign languages, and the ability to focus and concentrate. This research suggested the need for appropriate intervention strategies to minimize the negative impacts while maximizing the positive benefits of online games among generation Z